NUMERICAL SIMULATION ON THE TENSILE STRAIN HARDENING BEHAVIOUR OF ENGINEERED CEMENTITIOUS COMPOSITES (ECC) (Jurnal Teknologi (Sciences & Engineering), 2022)
Numerical simulation for evaluating tensile strain hardening behaviour of engineered cementitious composites (ECC) materials are extremely limited. This paper presents a finite element (FE) model developed to determine the multiple-cracking and strain hardening behaviour of ECC under uniaxial tension. A nonlinear FE program, ATENA was used in this study. A constitutive law based on individual crack-based model derived by the traction-separation relationship, or also known as tensile function was implemented in the model. Model calibration with parameter modifications were illustrated. The final simulation result predicts accurately the experiment tensile stress strain curves, including the tensile strain hardening response, ultimate tensile strength and tensile strain capacity. This includes validation from ECC specimens tested by various researchers. It has found that accuracy of the model is improved by lowering the crack opening displacement corresponds to the first cracking. The finding from this study would be useful in the future for further parametric analyses and structural optimization design of ECC members.